A localized non-healing ulcer: an unusual clinical presentation of pemphigus vulgaris - Brar, Sukhmani K.; Bhale, Gauri N.; Brar, Balvinder K. (International Journal of Research in Dermatology, 2020)
Pemphigus vulgaris is an autoimmune blistering disorder commonly involving oral mucosa and skin with characteristic acantholysis that results in formation of fluid filled blisters and painful erosions. Herein we report a case distinguished by its unusual clinical presentation. A twenty-five year old man, presented to our outpatient department of dermatology, complaining of ulcer on forehead in the last one year. Examination revealed single ulcer covered with crust on right side of forehead. Clinically lupus vulgaris, pyoderma gangrenosum, recurrent herpes simplex, leishmaniasis and pemphigus vulgaris were kept as differential diagnosis. Tzanck smear revealed multiple acantholytic cells and mild neutrophilic inflammatory infiltrate. Histological examination of biopsy sample showed suprabasal clefting, acantholytic cells and mild perivascular dermal lymphocytic infiltrate. Features were suggestive of pemphigus vulgaris. Significant improvement occurred after three months of treatment with oral prednisolone, azathioprine and topical steroid. Although oral and skin involvement is common, in the form of flaccid blisters and erosions, but non healing ulcer is unusual. This may represent a period of limited activity during this chronic disease. There is paucity of data in literature regarding this. So, this case report highlights a, perhaps unique, clinical presentation of this autoimmune disease.